2010
DOI: 10.1159/000318780
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotics Reduce Pancreatic Necrosis in Acute Necrotizing Pancreatitis: A Meta-Analysis of Randomized Trials

Abstract: Background and Aim: The use of prophylactic antibiotics to prevent infection and reduce mortality in patients with acute necrotizing pancreatitis (ANP) remains controversial. The aim of this study is to perform a systematic review of the data from randomized controlled trials to compare prophylactic antibiotic treatment of patients with ANP versus placebo. Methods: A computerized literature search was conducted using Medline, PubMed, EMBase and Cochrane Central Register of Controlled Trials (CENTRAL) for relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 67 publications
(55 reference statements)
2
25
0
2
Order By: Relevance
“…Overall, 6 of the 18 studies concluded that prophylactic antibiotics significantly reduced total mortality, which includes 17 RCTs, 18,[20][21][22][23][24] while 4 studies concluded that prophylactic antibiotics significantly reduced the incidence of pancreatic necrosis. 18,20,25,26 The two most recent studies included, 20,21 supported the use of antibiotics. Ukai et al 20 included six RCTs in which antibiotics (within 72 hours) were administered early in patients with acute necrotising pancreatitis, with the exclusion of studies with delayed or indeterminate timing of antibiotic administration.…”
Section: Mortality In Pancreatitis: Are Antibiotics Protective?mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 6 of the 18 studies concluded that prophylactic antibiotics significantly reduced total mortality, which includes 17 RCTs, 18,[20][21][22][23][24] while 4 studies concluded that prophylactic antibiotics significantly reduced the incidence of pancreatic necrosis. 18,20,25,26 The two most recent studies included, 20,21 supported the use of antibiotics. Ukai et al 20 included six RCTs in which antibiotics (within 72 hours) were administered early in patients with acute necrotising pancreatitis, with the exclusion of studies with delayed or indeterminate timing of antibiotic administration.…”
Section: Mortality In Pancreatitis: Are Antibiotics Protective?mentioning
confidence: 99%
“…As mentioned above, 6 of the 18 studies included in the current review were associated with reduced mortality when prophylactic antibiotics were used and the remaining 12 meta-analyses did not recommend the use of prophylactic antibiotic as there was no significant reduction in mortality with them. [25][26][27][30][31][32][33][34][35][36][37][38] These meta-analyses used a combined total of 14 RCTs with total study population varied from 329 to 841 patients.…”
Section: Mortality In Pancreatitis: Are Antibiotics Protective?mentioning
confidence: 99%
“…This is still a much debated issue, given the fact that a great number of papers, with remarkable heterogeneities in experimental designs and clinical groups addressing this question have been published so far. More notably, a group of recently published meta-analyses have failed to show a convincing role for prophylactic antibiotics in these patients, and since then, most groups have moved towards abolishing this practice [18,19,20,21]. Alternatively, the use of non-absorbable antibiotics via the oral route (selective digestive decontamination) as a strategy to reduce the rates of pancreatic necrosis has been recently proposed with some promising results [22,23].…”
Section: Antibiotic Therapy In Sapmentioning
confidence: 99%
“…Although polymicrobial infections caused by anaerobes and aerobes, including Escherichia coli, Enterobacter cloacae, Enterococcus faecalis, and Bacteroides fragilis are frequent in patients with SAP (2, 4, 13, 19), antibiotic prophylaxis is not recommended; however, in case of infectious complications, treatment with, e.g., a fluoroquinolone or a carbapenem is indicated (1,4,12,16,21,23,25).…”
mentioning
confidence: 99%
“…There is a 40 to 60% risk of pancreatic infections in patients with necrotizing pancreatitis, so antibacterial treatment is justified. Actually, carbapenems or ciprofloxacin are recommended (1,5,12,21,25). However, in contrast to ciprofloxacin, moxifloxacin is active against anaerobes; furthermore, its pharmacokinetic profile is more favorable than that of ciprofloxacin, as the concentrations of moxifloxacin in pancreatic tissue exceed the corresponding serum concentrations 3-fold (22), compared to a 1:1 ratio for ciprofloxacin (6,15).…”
mentioning
confidence: 99%